Will Argentina become a relevant gas exporter? - Roberto Carnicer; Ieda Gomes (The Oxford Institute for Energy Studies, 2021)
Argentina is the largest gas market in South and Central America, with demand in excess of 41 bcm/year in 2020, which is comparable to the size of the French gas market. The discovery and development of Vaca Muerta world class unconventional gas resources created expectations that Argentina would not only be self-sufficient but also become a pipeline and LNG exporter. In the 90's Argentina was a beacon for energy reform liberalisation and a solid pipeline exporter, but a fragile macro-economic environment coupled to continuous government interference on gas and energy prices led to a growing dependence on natural gas and liquids imports. This paper authored by Roberto Carnicer, Director of Energy at the Austral University, and Ieda Gomes, Senior Visiting Fellow of the OIES, focusses on the impact of successive regulatory changes on supply and demand, imports and exports. The paper also provides an assessment of the most recent gas plan aiming to encourage producers to meet priority demand in the residential and power sectors. The authors also analyse potential export markets for natural gas, if resources are fully developed, including petrochemicals, fertilizer and LNG. The paper provides an insight on the key issues impacting the development of LNG projects, including domestic demand seasonality and the need for new infrastructure. The authors concluded that “Argentina has certainly world-class gas resources and it has proved its capability to export gas to multiple markets." Hence, it is imperative to provide a reliable and long-lasting price policy and export regulatory framework as well as adequate financing mechanisms for the required infrastructure.
Keywords: 330; Argentina; LNG; Natural gas; natural gas pipelines; price regulation; regional exports; Shale gas; South America; Unconventional gas; Vaca Muerta